2007
DOI: 10.1128/jb.00188-07
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Antitermination by Translation Initiation Factor IF1

Abstract: Bacterial translation initiation factor IF1 is an S1 domain protein that belongs to the oligomer binding (OB) fold proteins. Cold shock domain (CSD)-containing proteins such as CspA (the major cold shock protein of Escherichia coli) and its homologues also belong to the OB fold protein family. The striking structural similarity between IF1 and CspA homologues suggests a functional overlap between these proteins. Certain members of the CspA family of cold shock proteins act as nucleic acid chaperones: they melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 45 publications
2
41
0
Order By: Relevance
“…These results suggest that the transcription antitermination activity of S10 is independent of ribosomes or ribosome-bound S10, in agreement with our finding that S10 cannot bind to NusB and the 30S subunit at the same time. The above results also suggest that under normal growth conditions, rRNA transcription antitermination is not essential and that proteins involved in antitermination are required because of their role in other cellular processes, as recently also shown for other antitermination factors (Bubunenko et al, 2007; Phadtare et al, 2007). …”
Section: Discussionsupporting
confidence: 77%
“…These results suggest that the transcription antitermination activity of S10 is independent of ribosomes or ribosome-bound S10, in agreement with our finding that S10 cannot bind to NusB and the 30S subunit at the same time. The above results also suggest that under normal growth conditions, rRNA transcription antitermination is not essential and that proteins involved in antitermination are required because of their role in other cellular processes, as recently also shown for other antitermination factors (Bubunenko et al, 2007; Phadtare et al, 2007). …”
Section: Discussionsupporting
confidence: 77%
“…It should be noted that the structure of the CSD domains is very similar to the structure of the S1 domain. On the basis of this similarity, the CSD and S1 domains are grouped into the OB (oligomer binding) fold (33), and the S1 domain proteins have been shown to exhibit in vivo and in vitro activities similar to those of CSD domain proteins (38,56,58). Therefore, it can be concluded that RNase R actually contains three CSD domains.…”
Section: Resultsmentioning
confidence: 99%
“…RNase R has three cold shock domains, the CSD1, CSD2, and S1 domains. Our previous study showed that CSD domains can act as nucleic acid chaperones and unwind RNAs (4,(36)(37)(38)(39)(40). Based on the in vivo data, the CSD2 domain seems to be critical for the helicase activity of RNase R and either the CSD1 or S1 domain is required for optimal activity.…”
Section: Resultsmentioning
confidence: 99%
“…IF1 is active in trans-splicing, it rescues the splicing of a misfolded intron in vivo, and it resolves a terminator stem in vitro and in vivo. 29,69 CspA has further striking similarity (43% sequence identity) to the cold shock domain of the Y-box factors, which are eukaryotic nucleic acid binding proteins involved in transcriptional and translational regulation. 70 One well-studied member is the major messenger ribonucleoprotein particle protein p50, also known as YB-1, which is a general regulator of translation by modulating mRNA structural rearrangements and packaging.…”
Section: Classification Of Proteins With Rna Chaperone Activitymentioning
confidence: 98%